Genetic variations related to inflammation in suicidal ideation and behavior: A systematic review - Tamimou, Rabah; Lumbroso, Serge; Mouzat, Kevin; Lopez-Castroman, Jorge (Frontiers in Psychiatry, 2022)
Background/Objectives Immune-inflammatory changes have been found in all types of suicidal ideation and behavior (SIB), independently of associated mental disorders. Since several Single Nucleotide Polymorphisms (SNPs) affect the function of inflammation-related genes, we searched the literature for genetic variations potentially altering inflammatory processes in SIB. Methods We included studies that looked for associations between SIB and SNPs in genes related to inflammatory processes. Case reports, literature reviews, and animal studies were excluded. Articles were retrieved from PubMed and PsycINFO databases, Google Scholar and GreySource Index until September 17th, 2022. Quality was assessed using Q-Genie. Results We analyzed 32 studies. SIB has been associated with eighteen SNPs located in genes encoding for interleukin-8 (rs4073), C-reactive protein (rs1130864), tumor necrosis factor α (rs1800629, rs361525 and rs1099724), tumor necrosis factor receptor 2 (rs1061622), transforming growth factor β-1 (rs1982073), acid phosphatase 1 (rs7419262, rs300774), interleukin-10 (rs1800896), interferon γ (rs2430561), amino-carboxy muconate semialdehyde decarboxylase (rs2121337), interleukin 7 (rs10448044, rs10448042), macrophage migration inhibitory factor (rs755622), interleukin 1-α (rs1800587) and interleukin 1-β (rs1143634 and rs16944. A genome-wide association study reported one association at the threshold of significance with the rs300774 SNP, located in the 2p25 region containing ACP1 gene. Discussion The studies included were methodologically and clinically diverse and of moderate quality. Their findings suggest that some inflammation-related SNPs could increase the likelihood of SIB but the evidence to date is insufficient. Further research using gene-gene (GxG) and gene-environment (GxE) approaches is warranted.